Animal’s Protection for Environmental Sustainability: An Islamic Perspective (Al-Qamar, 2020)
Animals’ protection is crucial for environmental stability and sustainability. Animals are the sign of magnificence and benevolence of Allah Almighty. The divine teachings of Islam provide a complete code for the welfare and protection of animals. Today the world has recognized the need for animals’ protection to maintain ecological balance. The ecological scientist has laid stress on animal rights and there is a great debate over the basic rights and liberties of animals. In the last few decades, humans have made great tremendous achievements in providing legal rights and protection to animals such as the “Universal Declaration on Animal Welfare”. The roots of recent animals protection and welfare paradigms can be traced back to Islamic injunctions provided 1400 years ago. Though man has subjugated animals still he is not authorized to do anything to animals. Environmental equilibrium will be damaged if animals are extinct as they are a part of the genesis pyramid. Islamic sacred scripture provides privileges and protection to animals. According to Islam, animals’ manipulation by man must be lawful as he will be accountable for that.  In the contemporary world, there exist diverse legislation, practices, and concerns regarding animals’ protection and rights. Highlighting some of these legislations, practices, and concerns, this article will provide an overview of Islamic teachings regarding animal protection and welfare that is much needed for biosafety today.
Keywords: Animal; Protection; Rights; Legislation; Environment; Islam